A Review of Challenges of Medical Education in the COVID-19 Crisis - Samaneh Sabet Birjandi; Afrooz Mazidimoradi (Health Technology Assessment in Action, 2022)
Abstract Before the outbreak of COVID-19 pandemic and due to the clinical nature of education in medical sciences, online and virtual educations were not implemented as the dominant methods in medical education; however, they were adopted as immediate solutions to help students pursue their education during the pandemic period. The change from the traditional education method to the electronic and virtual ones represented many challenges for the educational systems. The main challenges can be categorized into four groups: mental health consequences resulting from the quarantine and catching COVID-19, challenges of virtual education, challenges of clinical education, and challenges concerning medical students and COVID-19 frontline. In sum, the COVID-19 crisis was found to pose a number of challenges to faculty and students of medical science as well as to their families. In order to increase the preparedness of the medical education system to cope with similar crises, it was suggested that combined education programs should be implemented in the post-crisis period. Keywords: Medical Education, COVID-19, Virtual Education, Clinical Education